Genomic analysis of human and mouse TCL1 loci reveals a complex of tightly clustered genes - Hallas, Cora (The National Academy of Sciences, 1999)
TCL1 and TCL1b genes on human chromosome 14q23.1 are activated in T cell leukemias by translocations and inversions at 14q32.1, juxtaposing them to regulatory elements of T cell receptor genes. In this report we present the cloning, mapping, and expression analysis of the human and murine TCL1/Tcl1 locus. In addition to TCL1 and TCL1b, the human locus contains two additional genes, TCL1-neighboring genes (TNG) 1 and 2, encoding proteins of 141 and 110 aa, respectively. Both genes show no homology to any known genes, but their expression profiles are very similar to those of TCL1 and TCL1b. TNG1 and TNG2 also are activated in T cell leukemias with rearrangements at 14q32.1. To aid in the development of a mouse model we also have characterized the murine Tcl1 locus and found five genes homologous to human TCL1b. Tcl1b1–Tcl1b5 proteins range from 117 to 123 aa and are 65–80% similar, but they show only a 30–40% similarity to human TCL1b. All five mouse Tcl1b and murine Tcl1 mRNAs are abundant in mouse oocytes and two-cell embryos but rare in various adult tissues and lymphoid cell lines. These data suggest a similar or complementary function of these proteins in early embryogenesis.